G446(P) Promoting engagement of children and young people in allergy clinic via real time feedback tools and social media. (27th April 2015) - Brightwell, A; Watkins, C; Chapman, J
Abstract : Background: Research shows that patients consider their overall experience of care to be of equal importance in quality, alongside clinical effectiveness and safety. 1 The NHS constitution commits providers to encourage and welcome feedback on patients' healthcare experiences. 2 The difficulty of hearing the voices of children and young people as users of NHS services is widely acknowledged, and finding better ways to collect feedback from children and developing the use of IT in feedback have been identified as key priorities. 3 Aim: We aimed to improve the collection of patient feedback in our district general hospital allergy clinic to promote engagement of children, young people and families. Methods: All children, young people and families attending a district general hospital 'one stop' multidisciplinary children's allergy clinic were invited to submit real time feedback using a 'business card' feedback tool. Participants were encouraged to submit brief one or two word feedback. Responses were then summarised using a 'word cloud' and were made freely available on social media and displayed weekly in allergy clinic. Patients and families are also invited to submit feedback via twitter. Results: The real time feedback tool has now been running for 18 months. Seasonal themed word clouds are generated to capture the attention of children and young people. Following a number of comments regarding the length of waiting time, pre–clinic information has now been developed to give more information on what to expect on the day of the appointment, including expected duration of visit. Conclusion: Collection of real time feedback using a business card tool and displaying via a word cloud on social media is a novel, feasible and popular method of collecting patient feedback in a paediatric allergy clinic which has led to service improvement and aligns with NHS priorities for engagement with children and young people. References: Cornwell J. What matters to patients? developing the evidence base for measuring and improving patient experience. National Nursing Research Unit, King's College London. Coventry: NHS Institute, 2011 Web publication NHS Constitution, Department of Health 2013 Evans R. Celebrating the best of children and young people's experience of care. Patient Experience Network, NHS England, September 2013